Seismic Behaviour of Reinforced Concrete Buildings Under Dynamic Frequency Pattern by Using Etabs For (G+10) Sections In Zone V - Nirmal, Pradeep Kumar; Mire, Anisha; Singh, Lokesh (International Journal of Scientific Research in Civil Engineering, 2020)
Earthquake is the result of sudden release of energy in the earth’s crust that generates seismic waves. Ground shaking and burst are the significant impacts produced by tremors. It has social just as monetary outcomes, for example, causing passing and injury of living things particularly individuals and harms that assembled and regular habitat. In order to take precaution for the loss of life and damage of structures due to the ground motion, it is important to understand the characteristics of the ground motion. Earthquakes are one of the greatest natural disasters to human life and properties. Following lessons from previous earthquake disasters, the performance-based seismic design is increasingly accepted by engineers to prevent seismic disasters. In performance-based seismic design, realistic and reliable design response spectra are required to reliably and accurately predict responses of designing structures.
Keywords: Earthquake; Generates Seismic Waves; Disasters